2020
DOI: 10.1111/eva.12917
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure and predominance of cyclical parthenogenesis in the bird cherry‐oat aphid Rhopalosiphum padi in England

Abstract: Genetic diversity is the determinant for pest species' success and vector competence. Understanding the ecological and evolutionary processes that determine the genetic diversity is fundamental to help identify the spatial scale at which pest populations are best managed. In the present study, we present the first comprehensive analysis of the genetic diversity and evolution of Rhopalosiphum padi, a major pest of cereals and a main vector of the barley yellow dwarf virus (BYDV), in England. We have used a geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…In addition, seven RpCSPs shared one conserved amino acid proline between the second and third "C". The seven CSP genes sequences were further confirmed by analyzing the R. padi genome published by Thorpe et al (2018) and Morales-Hojas et al (2020).…”
Section: Identification and Characteristics Of Csp Genesmentioning
confidence: 87%
See 1 more Smart Citation
“…In addition, seven RpCSPs shared one conserved amino acid proline between the second and third "C". The seven CSP genes sequences were further confirmed by analyzing the R. padi genome published by Thorpe et al (2018) and Morales-Hojas et al (2020).…”
Section: Identification and Characteristics Of Csp Genesmentioning
confidence: 87%
“…Thorpe et al (2018) andMorales-Hojas et al (2020). Phylogenetic analysis indicated that the seven RpCSPs clustered in different clades (Fig.2).…”
mentioning
confidence: 99%
“…Furthermore, little is known about the genetic divergence of this aphid. On the other hand, most genetic studies of R. padi have focused on its life cycles or combination of life cycles and geographical locations [ 2 , 13 , 26 , 37 , 38 , 39 , 40 ], rather than the geographical locations alone [ 15 , 20 ]. There are four types of reproductive modes of R. padi in China [ 41 ]: (1) cyclical parthenogenesis; (2) obligate parthenogenesis; (3) mixture of cyclical parthenogenesis and obligate parthenogenesis; (4) obligate parthenogenesis with male production.…”
Section: Introductionmentioning
confidence: 99%
“…There are four types of reproductive modes of R. padi in China [ 41 ]: (1) cyclical parthenogenesis; (2) obligate parthenogenesis; (3) mixture of cyclical parthenogenesis and obligate parthenogenesis; (4) obligate parthenogenesis with male production. In addition, markers such as RAPD [ 23 ], SSR [ 6 , 26 , 42 ], ISSRs [ 25 ], and mtDNA (mitochondrial DNA) [ 20 , 38 ], as well as the genotyping-by-sequencing approach [ 39 ], have been applied to reveal genetic variations of R. padi . So far, only two studies on the genetic differentiation of R. maidis based on allozymes [ 43 ], mtDNA, and chromosome number [ 21 ] have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Aphids are among the most important cereal pests worldwide, inflicting economic damage directly through feeding and through the spread of viruses. In temperate regions, the bird cherry-oat aphid, Rhopalosiphum padi, is one of the most important cereal pests (Morales-Hojas et al, 2020;Trębicki, 2020). It is distributed in all wheat growing regions worldwide and is the main vector of Barley yellow dwarf virus (BYDV), responsible for significant losses in cereal yield and quality (Smith and Sward, 1982;Jones and Naidu, 2019).…”
Section: Introductionmentioning
confidence: 99%